Ответ:
Пошаговое объяснение:
= (10. 15/19 + 12. 4/19) + (-43. 8/13 +
(-56. 5/13)) =
22. 19/19 + (-43. 8/13 - 56. 5/13) =
23 + (-99. 13/13) = 23 + (-100) =
23 - 100 = -77
= (10 15/19+12 4/19)+(-43 8/13+(-56 5/13))
= 23+(-100)
= 23-100=-77
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
= (10. 15/19 + 12. 4/19) + (-43. 8/13 +
(-56. 5/13)) =
22. 19/19 + (-43. 8/13 - 56. 5/13) =
23 + (-99. 13/13) = 23 + (-100) =
23 - 100 = -77
Ответ:
Пошаговое объяснение:
= (10 15/19+12 4/19)+(-43 8/13+(-56 5/13))
= 23+(-100)
= 23-100=-77